(untitled) (Journal of Asian Development Studies, 2013)
The main purpose of the present study is to investigate possible effects of socio-demographical characteristics of healthcare professionals on their perceptions of patient safety level, patient safety culture, causes of medical errors and witnessing to/reporting medical errors in hospitals. A survey was conducted over 1,028 healthcare professionals of a large government-based university research hospital in Turkey. 786 people responded with a resulting usable response rate of 76.45%. According to the results, the health employee’s number of written medical error reports and perceived degree of patient safety influence his/her perception of the level of the patient safety culture. The health employee’s age, weekly working hours and number of years in the same hospital impact the perceived importance of the causes of medical errors. Healthcare professionals who received formal training on patient safety and/or see their organization as a workplace with a strong patient safety culture are more likely to notice and report medical errors and view the level of patient safety within their organization positively.